The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Klarius Mikkelsen's landing site: some further notes on the 1935 Norwegian visit to the Vestfold Hills, East Antarctica - Norman, Frederick Ian; Gibson, John A E; Jones, R T; Burgess, J S (Polar Record, 2002)
Further details regarding the landing made by Klarius Mikkelsen in the Tryne Islands, Vestfold Hills, East Antarctica, are given, being derived mainly from newspaper accounts made by Leif Sørsdal. All involved in the landing on 20 February 1935 have been identified, details of material left in the depot under the raised flag are given, and more extended information relating to the voyage to and from the site and the area generally are presented. Some comparison is made between Sørsdal's accounts and others. While the national importance of the landing was commented on, only Sørsdal apparently realised (but did not state) the insular nature of the site. Recent observations at the site suggest that its location is 68°22′38.22″S, 78°24′50.10″E, rather than that previously stated; bracing of the flagpole itself has been modified at some stage since its erection. Finally, some discussion is made regarding on-going questions relating to the accepted time on board ship, and possible consequences of errors.
Publisher: Cambridge University Press
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser